ANALISIS MAKNA KONTEKSTUAL PADA IKLAN NIAGA DI HARIAN ANALISA MEDAN - NETI TITIN JUNIAR (JURNAL SASTRA INDONESIA (SASINDO), 2014)
The title of this study "Analysis of the Meaning of Contextual Advertising Commercial Daily Issue Field Analysis". This type of research used by the author is descriptive method with qualitative approach. This study aimed to systematically describe the data collected and then researched and produced scientific data description. Sources of data in this study were obtained from commercial advertising in the Daily Field Analysis. Data that have been collected and analyzed using the theory and the semantic approach based on the meaning Contextual.The results of this study indicate that commercial advertisement, published in the Daily Field Analysis of data by 22 commercial ads were netted, all have meaning and purpose. Message or intent to convey the producers poured through texts and associated images. Meaning contained in the text or image associated with commercial advertising serves to introduce the product and influence the public or the reader to consume it openly. The contextual meaning is significant commercial advertising offers convenience, advanced in technology, advocacy, offering sophisticated services, the suggestion to use product, advanced technology, offering convenience and service, and most importantly advertising on commercial advertising, namely how to attract the attention of consumers. If the community has been affected even buy the product then the purpose of the advertisement is reached.Keywords: Advertising, semantics, meaning, newspapers